The Theological Bearing of Puranic Stories: An Enquiry into the Presence of Feminine Theology in the Brahma-vaivarta-purana - Gielen, Joris (Religions of South Asia, 2010)
In Western indological literature the term ‘theology’ is often used to analyse descriptions of Hindu gods and their attributes. Western scholars have likewise retrieved a theology focusing on Radha in various texts, notably in the Brahma-vaivarta-purana. In this purana a feminine theology is said to have been developed. The aim of the present study was to assess whether a feminine theology is present in the Brahma-vaivarta-purana and to evaluate whether our understanding of the purana as a theological or non-theological text could enhance our understanding of Hinduism. Both predicates ‘feminine’ and ‘theological’ are problematic with regard to the purana. The purana can only with difficulty be called feminine because women are not always respectfully approached and Radha is not consistently portrayed as superior or equal to Krsna. Since the purana links Radha with the theologically important functions of creation and redemption, the text seems theological. Yet logical inconsistencies make the term theology also unsuitable for the purana. If this purana and other similar texts are not theology, they cannot be used to solve theological problems like the relationship between divine nature and ethics. Hence, there is no contradiction between Radha’s elevated position in some texts and a secondary treatment of women.